Compositional Processing Emerges in Neural Networks Solving Math Problems - Russin, Jacob; Fernandez, Roland; Palangi, Hamid; Rosen, Eric; Jojic, N.; Smolensky, Paul; Gao, Jianfeng (CogSci ... Annual Conference of the Cognitive Science Society. Cognitive Science Society (U.S.). Conference, 2021)
A longstanding question in cognitive science concerns the learning mechanisms underlying compositionality in human cognition. Humans can infer the structured relationships (e.g., grammatical rules) implicit in their sensory observations (e.g., auditory speech), and use this knowledge to guide the composition of simpler meanings into complex wholes. Recent progress in artificial neural networks has shown that when large models are trained on enough linguistic data, grammatical structure emerges in their representations. We extend this work to the domain of mathematical reasoning, where it is possible to formulate precise hypotheses about how meanings (e.g., the quantities corresponding to numerals) should be composed according to structured rules (e.g., order of operations). Our work shows that neural networks are not only able to infer something about the structured relationships implicit in their training data, but can also deploy this knowledge to guide the composition of individual meanings into composite wholes.